Technological Review Of The All-Hydraulic Rock Drills - I. Introduction - R. L. Bullock (Society for Mining, Metallurgy & Exploration, 1975)
For many years, the combined efforts of machinery manufacturers and mine operators have endeavored to achieve greater productivity from the men involved and the machinery and capital invested, by developing methods to drill blast holes more effectively. Obviously, this means much more than simply developing a drill that will drill a single hole faster. Considerable attention over these years has also been given to methods of carrying and positioning the drilling machine on versatile jumbos, whereby the man's time can he better utilized by the faster drilling machines. Likewise, the art of blasting to utilize the holes that were drilled to achieve the maximum amount of fragmented ore and the methods of moving the broken ore have also progressed. But each phase of the production cycle just described must be made to balance with the other phases of the work. Obviously, major breakthroughs in only one phase don't always generate more "rock in the box" per manshift. Yet, through the persistent effort of the machinery developers and the researchers, the progressive attitudes of mine managers, backed by corporate capital investments, and battle after battle at the operating level, progress is made. Then, if the innovated system is good enough to "stick", in a few years it becomes the system that the newer method must replace, after the same repeated struggle. This is the situation that many mine operators find themselves in today, Looking at their production cycle, which is assumed to be efficient and balanced between drilling, blasting and materials moving capabilities, they tend to guard any visable disruption of the balance of that day's production, and many would prefer to maintain the status quo indefinitely. Yet, if history repeats itself, we can expect any major breakthrough in the cycle to trigger other innovations in the